Pengaruh Prenatal Yoga Terhadap Tingkat Kecemasan dalam Menghadapi Persalinan pada Ibu Primigravida - Dianna; Desy Rosita; Ahmariska Junandar; Arlina Rachmaida (STIKES Bina Usada Bali, 2026)
Background: Psychological conditions such as anxiety and depression may occur in mothers experiencing illness as well as pregnancy and childbirth complications. One non-pharmacological method that can help women focus on labor, prepare to tolerate pain, and transform stress and anxiety into energy is the practice of gentle yoga during pregnancy. This study aims to analyze the anxiety levels of third-trimester primigravida mothers before and after receiving prenatal yoga intervention in facing childbirth in the working area of UPT Puskesmas Kom Yos Sudarso. Methodology: This study used a one-group pre-test and post-testt design to measure anxiety levels using a questionnaire administered before and after the intervention. The sampling technique resulted in a total of 31 respondents. Result: The paired t-test showed a p-value of 0.000, indicating that prenatal yoga has a significant effect in reducing anxiety among third-trimester primigravida mothers. Conclusions: There is a difference in anxiety levels among third-trimester primigravida mothers before and after receiving prenatal yoga intervention in the working area of UPT Puskesmas Kom Yos Sudarso.